Fine structure of the lunar crust and upper mantle in the mare serenitatis derived from gravity multi-scale analysis - Yu, Hangtao; Xu, Chuang; Wu, Yihao; Li, Jinbo; Jian, Guangyu; Xu, Ming (Frontiers in Astronomy and Space Sciences, 2023)
It is significant for revealing the formation mechanism of the lunar Mascon to invert the refined 3-D lunar crust and upper mantle structure of the Mare Serenitatis. As the development of space exploration technology, lunar gravity data has advantages of high accuracy and resolution, which can be used to invert the lunar crust and upper mantle structure. However, gravity anomaly reflects all anomalous material during the whole Moon’s interior, and its vertical structure recognition capability is poor. Thus, this paper adopts wavelet multi-scale analysis method to decompose the gravity anomaly in the Mare Serenitatis for enhancing vertical resolution, and the corresponding field source depths of the decomposed gravity anomalies are further estimated by power spectrum method. Subsequently, the layered densities and the crust-mantle interface depth of the Mare Serenitatis are inverted. The research results show that the 3-D morphological character of two large high-density materials in the Mare Serenitatis is clearly depicted. The southwest high-density material with its bottom center at approximately (15 °E, 25 °N) has the depth range of 50 km - 80 km and the maximum diameter of approximately 150 km. As for the southeast high-density material, its bottom center is located at approximately (23 °E, 25 °N), the depth range is 30 km - 60 km and the maximum diameter is approximately 100 km. Another new finding is that the crust-mantle interface uplift has obviously fallen back in the center of the Mare Serenitatis. The high-density materials and crust-mantle interface uplift may together promote the formation of the Mascon in the Mare Serenitatis.